Heavily Graphitic-Nitrogen Self-doped High-porosity Carbon for the Electrocatalysis of Oxygen Reduction Reaction - Tong Feng; Wenli Liao; Zhongbin Li; Lingtao Sun; Dongping Shi; Chaozhong Guo; Yu Huang; Yi Wang; Jing Cheng; Yanrong Li; Qizhi Diao (Nanoscale Research Letters, 2017)
Abstract Large-scale production of active and stable porous carbon catalysts for oxygen reduction reaction (ORR) from protein-rich biomass became a hot topic in fuel cell technology. Here, we report a facile strategy for synthesis of nitrogen-doped porous nanocarbons by means of a simple two-step pyrolysis process combined with the activation of zinc chloride and acid-treatment process, in which kidney bean via low-temperature carbonization was preferentially adopted as the only carbon-nitrogen sources. The results show that this carbon material exhibits excellent ORR electrocatalytic activity, and higher durability and methanol-tolerant property compared to the state-of-the-art Pt/C catalyst for the ORR, which can be mainly attributed to high graphitic-nitrogen content, high specific surface area, and porous characteristics. Our results can encourage the synthesis of high-performance carbon-based ORR electrocatalysts derived from widely-existed natural biomass.